PENANAMAN NILAI-NILAI ISLAM DALAM MEMBENTUK SOPAN SANTUN ANAK DI RAUDLATUL ATHFAL AL-AZHAR MENGANTI - Muhamad Arif (UPI Kampus Cibiru, 2019)
Abstract: Phenomenon in one school in East Java, in contrast to RA Al-Azhar menganti, one of the RA in the Menganti area which is in the shade of Islamic boarding schools namely Islamic Boarding School Darul Ihsan. Early childhood at this school have different habits with children in school, such as in every picture of Islamic boarding school kyai walking past RA Al-Azhar building, children in this school spontaneously, without seeing the command from the teacher, they know scrambling to shake hands for clerics. Starting from the phenomenon in wanting to find out about Islam Islamic values in making polite in early childhood. as well as some challenges of the teacher in carrying out the process of Islamic values in early childhood at Al-Azhar Menganti Gresik's Raudlatul Athfal (RA). The research method used by researchers is a qualitative method, using phonology, by looking for data through interviews, observation and data source collection, after which data analysis is carried out from miles and links using data triangulation. The results show how to cultivate Islamic values in shaping the courtesy of children to conceptualize playing while learning, giving stories of exemplary, watching Islamic films while learning, providing complete examples continuously, so that they can be financed according to the child's own needs. While the teacher is the guardian of the student who does not pay attention to the child considering his various activities.Keywords: education, early childhood, polite manners